Presenting a city: Brussels and its subjective portraits - Anne Reverseau (Brussels Studies, 2019)
Based on BXL Universel – the first part of the trilogy of exhibits on Brussels proposed by CENTRALE for contemporary art – we explore the concept of an “exhibit/portrait of a city”. The 2017 exhibit met the challenge of presenting a city by making Brussels a “creative home port”, by showing the continuity between its past and its present, and by making portraits of it which were diverse as well as subjective. The exhibit created by Carine Fol is put into perspective, both in the context of other exhibits devoted to Brussels in recent years, and of recent research on portraits of territories. This article thus intends to lay the foundations for an analysis of exhibits/portraits of cities in general, and proposes several approaches to the specificity of Brussels as a city being presented, by insisting in particular on the significance of folklore, the foreign perspective and the collective dynamic.